El contexto de mujer en la realidad jurídico-penal colombiana: delitos sexuales y revictimización (2013)
Social interactions of female individuals are set by predetermined symbolic andcultural values of inferiority, weakness and other adjectives of subordination towomen, implicit in contexts learned in the various scenarios. The treatment ofsexual crimes in Colombia, mostly, involve women as victims; whoever the rule isconstructed regardless of the victim and it is not enough to avoid that, after primaryvictimization, double damage is made to the integrity and sexual freedom. It is clearthe necessity to change the social imaginary and the creation of positive actions tovindicate the rights of women.